2017
DOI: 10.1016/j.anai.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the black box of food allergy mechanisms

Abstract: Objective To review our current understanding of immunotherapy, the immune mechanisms underlying food allergy, and the methodological advances that are furthering our understanding of the role of immune cells and other molecules in mediating food allergies. Data Sources Literature searches were performed using the following combination of terms: allergy, immunotherapy, food, and mechanisms. Data from randomized clinical studies using state-of-the-art mechanistic tools were prioritized. Study Selections Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Herein, we demonstrate that IL-4 can amplify the IgE-mediated, histamine-induced fluid extravasation through priming of the vascular endothelial compartment. Previous studies have revealed an important role for IL-4 and IL-4Rα signaling in IgE-mediated anaphylaxis; however, this was predominantly thought to be through its effect on the hematopoietic compartment driving IgE-isotype switch and the associated CD4 + Th2 and mast cell response in anaphylaxis 31, 6769 . We show that IL-4 also acts on the non-hematopoietic compartment, namely the VE to increase the sensitivity of the VE to histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we demonstrate that IL-4 can amplify the IgE-mediated, histamine-induced fluid extravasation through priming of the vascular endothelial compartment. Previous studies have revealed an important role for IL-4 and IL-4Rα signaling in IgE-mediated anaphylaxis; however, this was predominantly thought to be through its effect on the hematopoietic compartment driving IgE-isotype switch and the associated CD4 + Th2 and mast cell response in anaphylaxis 31, 6769 . We show that IL-4 also acts on the non-hematopoietic compartment, namely the VE to increase the sensitivity of the VE to histamine.…”
Section: Discussionmentioning
confidence: 99%
“…CX3CR1+ macrophages can capture food antigens directly from the intestinal lumen by insinuating dendritic extensions between epithelial junctions (periscopic mechanism). CD103+ DCs transport the captured antigens to Peyer's patches and mesenteric lymphnodes and drive the homing of B lymphocytes secreting mucosal IgA in the gut, thus contributing to the maintenance of a specific immune tolerance [92]. IgGs, in particular, specific IgG4, can inhibit the initiation as well as the effector phases of allergic responses, thus also contributing to the acquisition of oral tolerance to food antigens [2].…”
Section: Tolerance Disruptionmentioning
confidence: 99%
“…Among the other cell types involved in tolerance disruption, innate lymphoid cells of type 2 (ILC2), similar to Th2 lymphocytes but lacking specificity for the antigen, and IL-9-producing cells (Th9 cells), which are mucosal mastcells capable of producing various inflammatory cytokines and capable to suppress the function of Tregcells, have been recently recognized [2,100]. All of them increase the vicious circle which leads, through an autocrine loop, to the increase in the intestinal mastcell pool [20,92,101].…”
Section: Tolerance Disruptionmentioning
confidence: 99%
“…Several Treg subtypes have been associated with tolerance, including Foxp3 + Tregs, IL-10-secreting Foxp3 -Tregs (also known as Tr1 cells), and TGF-β-secreting T helper 3 (Th3) cells. Further details can be found in a number of excellent reviews on the topic (46,48,(62)(63)(64)(65)(66)(67)(68).…”
Section: T Cell Mechanisms Underlying Tolerancementioning
confidence: 99%